2010
DOI: 10.1007/s00011-010-0224-2
|View full text |Cite
|
Sign up to set email alerts
|

Amebic monocyte locomotion inhibitory factor peptide ameliorates inflammation in CIA mouse model by downregulation of cell adhesion, inflammation/chemotaxis, and matrix metalloproteinases genes

Abstract: MLIF could be an interesting new molecule to investigate in the field of rheumatoid arthritis pathogenesis research for its potential to prevent inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous investigations have reported that MAPK pathway is involved in the biological actions of MLIF[ 46 ]. As a group of MAPK families, JNK pathway plays an important role in apoptosis by destabilize p53 and promote ubiquitin-mediated degradation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have reported that MAPK pathway is involved in the biological actions of MLIF[ 46 ]. As a group of MAPK families, JNK pathway plays an important role in apoptosis by destabilize p53 and promote ubiquitin-mediated degradation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that MLIF can inhibit the expression of interleukin-1␤, interferon-␥, interleukin-5, and interleukin-6 and increase the expression of interleukin-10 in macrophages. [11][12][13][14][15][16] The anti-inflammatory effect of MLIF led us to the initial interest to test whether it can act inflammatory response in brain ischemia. We 17 and other laboratories 18 have found MLIF can remarkably protect brain ischemic injury with decreased ischemic volume changes.…”
mentioning
confidence: 99%
“…Expression profiling by high throughput sequencing data sets was obtained from Gene Expression Omnibus (GEO). GSE14721: Articular tissue from collagen–induced arthritis (CIA) (vs. adjuvant ctrl) 27 ; GSE13071: Knee joint synovium from CIA (vs. naïve ctrl) 28 ; GSE167190: Whole ankle tissue from collagen antibody–induced arthritis (CAIA) (vs. LPS ctrl) 29 ; GSE71599: K/BxN serum–transfer arthritis (STA) synovium (vs. PBS ctrl) 30 ; GSE89408: RA synovial biopsies (vs. Osteoarthritis) 31 ; GSE77298: RA synovial biopsies (vs. healthy ctrl) 32 ( Figure 1A ). Enrichment analysis was performed using Metascape 33 ( https://metascape.org/ ) ( Figure 1B ).…”
Section: Methodsmentioning
confidence: 99%